SYNTHESIS OF SOME S-DERIVATIVES OF 1,2,4-TRIAZOLES (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
The reactions of 5-merkapto-3,4-disubstituted-1,2,4-triazoles with ethyl chloroacetate have been investigated. It has been shown that mercapto group reacted and S-substituted derivatives were formed. On the next step hydrazinolysis by 85% hydrazine hydrate was carried out and on the base of obtained hydrazides thiosemicarbazides were synthesized. Further by means of intermolecular cyclization bis-1,2,4-triazoles were obtained, structure of heterocyclic rings were connected by thio-methyl bridge.
Keywords: 1,2,4-triazoles, hydrazinoles, thiosemicarbazides, bis-triazoles